Communication and Social Interaction between Chinese and indigenous Ethnics in Bandar Lampung, Indonesia - Tina Kartika; Akhmad Syafrie; Nanda Utaridah; Fri Rejeki Noviera; Abdurrahman (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study discusses the language used and neighboring social interaction between the Chinese and the Indigenous Ethnics in Teluk Betung Selatan District, Lampung Province. The Indigenous Ethnics in this area consist of Lampung, Javanese, Minang, and Malay. Indonesia has a mixed population of racial and ethnic origins. Ethnicity, language, geography, and customs of each region make up the domestic background which includes indians, chinese, european, and arabs from outside Indonesia. Chinese and Indigenous Ethnics are represented in this study by ethnicity. The research uses a qualitative approach, data obtained from observations and interviews with 24 informants. The data analysis technique includes several stages, namely collection, reduction, and display of data. The findings show that the communication between the Chinese and the Indigenous Ethnics language use, if the Chinese communicate with Chinese, they use the Hokkien dialect for social relations/economic relations to support everyday life. In daily social activities, communication and social connections underpin economic relationships. Communication in social interaction must be managed properly or it will become a latent danger to the community’s harmony. The recommendation to the local government is to practice one day of the week to speak the local language and respect indigenous ethnicity.